Identification of signal quality around UiTM main campus / Muhammad Aizzad Mushaimi - Mushaimi, Muhammad Aizzad
As 3G networks are becoming commercially available all over Malaysia, all of the network providers compete to serve their customer with a good quality and stable network. This project is to analyze the 3(J's signal quality and strength that are provided by Maxis Sdn. Bhd around targeted area at LiTM Shah Mam. The collected data from the drive test by using NEMO outdoor network scanner was plotted using Microsoft Excel. The parameters that been focused for this project are Received Signal Code Power (RSC'P) which relates lo signal strength and Carrier to Noise Density ratio (Ec/No) that are representing the cell quality of the pilot channel (C'PIC'M).|3| Based from the graph obtained, we can see the relationship between each of the parameters that are being investigated.